First-in-human study of a novel cell death tracer [99mTc]Tc-Duramycin: safety, biodistribution and radiation dosimetry in healthy volunteers - Taco Metelerkamp Cappenberg; Stijn De Schepper; Christel Vangestel; Stef De Lombaerde; Leonie wyffels; Tim Van den Wyngaert; Jeffrey Mattis; Brian Gray; Koon Pak; Sigrid Stroobants; Filipe Elvas (SpringerOpen, 2023)
Abstract Background Imaging of cell death can provide an early indication of treatment response in cancer. [99mTc]Tc-Duramycin is a small-peptide SPECT tracer that recognizes both apoptotic and necrotic cells by binding to phosphatidylethanolamine present in the cell membrane. Preclinically, this tracer has shown to have favorable pharmacokinetics and selective tumor accumulation early after the onset of anticancer therapy. In this first-in-human study, we report the safety, biodistribution and internal radiation dosimetry of [99mTc]Tc-Duramycin in healthy human volunteers. Results Six healthy volunteers (3 males, 3 females) were injected intravenously with [99mTc]Tc-Duramycin (dose: 6 MBq/kg; 473 ± 36 MBq). [99mTc]Tc-Duramycin was well tolerated in all subjects, with no serious adverse events reported. Following injection, a 30-min dynamic planar imaging of the abdomen was performed, and whole-body (WB) planar scans were acquired at 1, 2, 3, 6 and 23 h post-injection (PI), with SPECT acquisitions after each WB scan and one low-dose CT after the first SPECT. In vivo 99mTc activities were determined from semi-quantitative analysis of the images, and time-activity curves were generated. Residence times were calculated from the dynamic and WB planar scans. The mean effective dose was 7.61 ± 0.75 µSv/MBq, with the kidneys receiving the highest absorbed dose (planar analysis: 43.82 ± 4.07 µGy/MBq, SPECT analysis: 19.72 ± 3.42 μGy/MBq), followed by liver and spleen. The median effective dose was 3.61 mSv (range, 2.85-4.14). The tracer cleared slowly from the blood (effective half-life of 2.0 ± 0.4 h) due to high plasma protein binding with < 5% free tracer 3 h PI. Excretion was almost exclusively renal. Conclusion [99mTc]Tc-Duramycin demonstrated acceptable dosimetry (< 5 mSv) and a favorable safety profile. Due to slow blood clearance, optimal target-to-background ratios are expected 5 h PI. These data support the further assessment of [99mTc]Tc-Duramycin for clinical treatment response evaluation. Trial registration: NCT05177640, Registered April 30, 2021, https://clinicaltrials.gov/study/NCT05177640 .